Classtime.Com as an Ai-Based Testing Platform: Analysing ESP Students’ Performances and Feedback - Fitria Ningsih (Journal of Languages and Language Teaching, 2023)
The use of Artificial Intelligence (AI) technology in education has grown in popularity, especially in online assessments. This research evaluates the effectiveness of an AI-based online testing platform, Classtime.com, in teaching tenses in English for Specific Purposes (ESP). The study uses a mixed-methods approach, collecting data from 246 Economic Sharia Law students who took the midterm exam during the 2022-2023 school year. The results show that the average score on the exam was 88.21, indicating a high overall performance. Females scored higher and more consistently than males. The study suggests that Classtime.com's AI-based testing is an effective tool for teaching tenses in ESP assessment, providing immediate feedback and personalized learning experiences. However, the study's focus on one language subject limits its generalizability to other subjects. Nevertheless, the use of AI-based online testing in ESP assessment can improve language learning outcomes and contribute to effective teaching practices. Future research should explore the use of AI-based online testing platforms in other language subjects, investigate factors influencing student performance, and examine long-term effects on language learning outcomes and attitudes toward language education and assessment.